Cimetidine Improves the Accuracy of Creatinine Clearance as an Indicator for Glomerular Filtration Rate - Choi, Ki Chul (Korean J Intern Med, 1993)
BACKGROUND: Although endogenous creatinine clearance is often used as an indicator for the glomerular filtration rate (GFR), it may result in an overestimation due to its tubular secretion. Since cimetidine is known to inhibit tubular secretion of creatinine, it may improve the accuracy of the creatinine clearance in measuring GFR. METHODS: Creatinine clearance (C(cr)) was compared with iothalamate clearance (C(10th)) during oral administration of either placebo or cimetidine in 25 patients with varying degrees of renal dysfunction. RESULTS: Cimetidine itself had no effect on C(10th) but decreased C(cr), improving its validity, as measured by a significant decrease of C(cr)/C(10th) from 1.72 during placebo to 1.17 during cimetidine administration. The degree of overestimation measured by the C(cr) was more pronounced in those with more severe renal dysfunction. A significant inverse correlation was noted between C(cr)/C(10th) and GFR. No apparent side effect due to cimetidine was noted. CONCLUSIONS: These results suggest that cimetidine improves the accuracy of C(cr) as an indicator for GFR in patients with varying degrees of renal dysfunction.